Level of Vulnerability and Adaptation to Climate Change Based on Rice Ecosystems - Aptiaty Kamaluddin; St. Hatidja; Hidayat Marmin; Lina Mariana (Manunggal Halim Jaya, 2021)
This study aims to assess farmers' vulnerability, resilience, and adaptation to climate change based on rice ecosystems. The information on vulnerability and adaptation to climate change in rice ecosystems obtained is expected to be helpful and become input for local governments and other stakeholders in making policies to support agricultural activities in regions in Indonesia, especially in the rice ecosystem. This research was conducted for six months, from February to September 2021. The assessment of farmers' vulnerability to climate change in the rice ecosystem uses three elements of exposure: outcrop, sensitivity, and adaptability. The research sample was taken from the rice production center in Takalar Regency, namely North Polombangkeng District. The study results show that the rainy zone is divided into two climates. Only a tiny part of the rice ecosystem community stated that they did not know about climate change. The impacts of climate change that respondents feel include decreased production (food crops and plantations), crop failure (puso) due to drought, and the reduced show that is the most touched by the rice ecosystem community. The cumulative index of sensitivity in the North Polmbangkeng sub-district is different. The categories are rather low class, relatively low class, and medium-class due to each sensitivity indicator's various weights and scores. Based on the value of the cumulative index of vulnerability and adaptive capacity, the three study districts range from vulnerable to very vulnerable. Lassang Village has the highest vulnerability index value (fragile) compared to the other two study districts, so it needs immediate attention.